Chad : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2007)
This Report on the Observance of Standards and Codes data module provides an assessment of Chad's macroeconomic statistics against the recommendations of the General Data Dissemination System complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that Chad's performance on macroeconomic statistics is weak in national accounts and government finance statistics. In addition, there is room for improvement in monetary and balance of payments statistics.